KONSEP MARKETING DALAM INOVASI PRODUK PERBANKAN SYARIAH - Himyar Pasrizal (Nizham Jurnal Studi Keislaman, 2013)
Business and banking competition getting tougher and dynamic with the flow ofmodernity, in which the bank is now not only save space but also as a place forinvestment and financial consulting making banking products in Indonesia increasinglyvaried to meet those needs. Product innovation is a keystone to the method of productdevelopment. Product innovation can deliver the product to be repackaged or newproducts. Product innovation is also done through the improvement or refinement ofexisting products, adding features, specifications and the resulting benefits. Islamicbanking should be careful in product innovation so that the demand for the productremains high. This means not only product innovation but rather product oriented tocustomer oriented. In other words, the development of innovative Islamic bankingproducts is consistent with the requirements (needs) and desires (wants) or taste currentcustomers. Which is more important in marketing and product innovation in Islamicbanking is how the product and the product innovation is not contrary to Islamic law orcontrary to the Qur'an and Sunnah. Product innovation must be done when the positionof the PLC is in decline sales.